Meat consumption & positive mental health: A scoping review - Urska Dobersek; Mary Bender; Alexandria Etienne; Gabriela E. Fernandez Gil; Claire Hostetter (Preventive Medicine Reports, 2024)
The objective of this scoping review was to examine the breadth of the existing literature on the relation between meat consumption or meat abstention and positive psychological functioning. In April 2022, we conducted a systematic search of online databases (PubMed, PsycINFO, CINAHL Plus, Medline, Cochrane Library, and Web of Science) for primary research examining positive psychological functioning in meat consumers and those who abstain from meat. Thirteen studies met the inclusion/exclusion criteria, representing 89,138 participants (54,413 females and 33,863 males) with 78,562 meat consumers and 10,148 meat abstainers (13–102 years) from multiple geographic regions. The primary outcomes were life satisfaction, “positive mental health”, self-esteem, and vigor. The secondary outcomes were “meaning in life”, optimism, positive emotions, and psychological well-being. Eight of the 13 studies demonstrated no differences between the groups on positive psychological functioning, three studies showed mixed results, and two studies showed that compared to meat abstainers, meat consumers had greater self-esteem, “positive mental health”, and “meaning in life”. Studies varied substantially in methods and outcomes. Although a small minority of studies showed that meat consumers had more positive psychological functioning, no studies suggested that meat abstainers did. There was mixed evidence for temporal relations, but study designs precluded causal inferences. Our review demonstrates the need for future research given the equivocal nature of the extant literature on the relation between meat consumption and meat abstention and positive psychological functioning.